Hawks Nest - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case looks at serious safety violations in the workplace, focussing on the example of a tunnel built by the engineering company Rinehart and Dennis in West Virginia. By cutting safety costs they saved money at the expense of their worker's lives and health.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Hawks Nest. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 225-257). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Industrial safety -- Management -- Case studies; Hawks Nest Tunnel (W. Va.) -- History